Congenital heart defects in orofacial cleft: A prospective cohort study - Olufemi A Erinoso; Olutayo James; Ogochukwu J Sokunbi; Olawale O Adamson; Adeola A Adekunle; Olusola F Agbogidi; Ajoke O Ogunlewe; Ekanem N Ekure; Wasiu L Adeyemo; Akinola L Ladeinde; Olugbemiga M Ogunlewe (Wolters Kluwer Medknow Publications, 2021)
Background: Congenital heart defects (CHDs) are one of the most common associated anomalies in patients with an orofacial cleft (OFC). However, few studies have shown the association between cleft type and CHDs in our population. This study aimed to assess the prevalence of CHDs in a cohort of OFC patients at a tertiary health facility in Nigeria, as well as assess the risk of CHD by OFC type. Materials and Methods: This was a prospective study design. Patients with an OFC were consecutively enrolled at a single OFC treatment facility. All subjects were assessed by a paediatric cardiologist and had echocardiography done. They were categorised based on the presence of CHDs, as well as the OFC phenotypic type (cleft lip and/or alveolus, cleft lip and palate and cleft palate only). Statistical analysis was done using STATA version 14 (College Station, Texas), and significance was set at P < 0.05. Results: A total of 150 subjects enrolled in the study over a period of 2 years (2018-2020). The median age of subjects was 6 months (interquartile range: 2-24), and 54.7% were female. The prevalence of CHDs in the subjects reviewed was 30.7%. Based on the severity of CHDs, the majority presented with simple defects (95.6%). Overall, the most common presentation was patent foramen ovale (12.7%), followed by septal defects (8.0%). There was no significant association between cleft type and the odds of a CHD. Conclusion: The study reports a relatively high prevalence of CHDs in patients with OFC; however, there was no association between the risk of CHD by cleft type. Although a majority of CHDs may pose a low operative risk, cardiac evaluation is recommended for all cases of OFC to aid the identification of potentially high-risk cases.